Biointerfacing Antagonizing T‐Cell Inhibitory Nanoparticles Potentiate Hepatocellular Carcinoma Checkpoint Blockade Therapy - Wu, Han; Zhu, Jia‐Qi; Xu, Xin‐Fei; Xing, Hao; Wang, Ming‐Da; Liang, Lei; Li, Chao; Jia, Hang‐Dong; Shen, Feng; Huang, Dong‐Sheng; Yang, Tian (Small (Weinheim an der Bergstrasse, Germany), 2021)
Hepatocellular carcinoma (HCC) is one of the most fatal malignancies with few effective treatment options all around the world. The efficacy of the arisen immune checkpoint therapy is still uncertain due to local immunosuppression. In order to further overcome T cell suppression in the tumor immune microenvironment while promoting the immune response of antigen‐presenting cells, a biointerfacing antagonizing T‐cell inhibitory nanoparticles (BAT NPs) has been developed by cloaking platelet membrane on the PLGA microsphere surface to load T‐cell immunoglobulin domain and mucin domain‐3 antibodies (anti‐TIM‐3) as well as PD‐L1. Notably, in addition to activating the proliferation and migration of T cells, the contained anti‐TIM‐3 can cooperate with PD‐L1 checkpoint blockade to exert therapeutic effects. Furthermore, the components of BAT NPs like anti‐TIM‐3 and platelet can act together for collagen deposition in tumor starvation treatment. Thus, a novel targeting therapeutic strategy that can effectively reverse the immune‐inhibiting microenvironment is effectively applied to PD‐L1 checkpoint combination therapy. Such therapeutic effect can subsequently activate the effector T lymphocytes and antigen presentation of dendritic cells as well as the polarization of M1‐type macrophages. Last, the study presented the synergistic effect of immune therapeutic adjuvants and BAT NPs components in achieving tumor inhibition and prolonging tumor‐burden survival. The biointerfacing antagonizing T‐cell Inhibitory nanoparticles (BAT NPs) are synthesized to participate in Hepatocellular carcinoma immunoregulatory therapy and tumor starvation therapy. The platelet membrane acts as a bionic and targeted function. BAT NPs can be combined with PD‐L1 checkpoint therapy to activate T cells, promote dendritic cells proliferation and M1 polarization, and the following collagen deposition contributes to starvation therapy.